2017
DOI: 10.1016/j.eururo.2017.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Updated Systematic Review and Meta-analysis of the Comparative Data on Colposuspensions, Pubovaginal Slings, and Midurethral Tapes in the Surgical Treatment of Female Stress Urinary Incontinence

Abstract: CONTEXT: Retropubic (RT-TVT) and transobturator miurethral (TO-TVT) mid-urethral sling (MUS) are popular surgical treatments for female stress urinary incontinence (SUI). The long-term efficacy and safety of the procedures is still a topic of intense clinical research and several randomized controlled trials (RCTs) have been published in the last years OBJECTIVE: To evaluate the efficacy and safety of MUS compared with other surgical treatments for female SUI. EVIDENCE ACQUISITION:A systematic review and meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(147 citation statements)
references
References 46 publications
(31 reference statements)
5
117
2
6
Order By: Relevance
“…More recently, the operation has been successfully used for primary SUI, as continence rates were better with greater patient satisfaction despite the higher incidence of postoperative voiding dysfunction compared with Burch colposuspension [3]. This finding is supported by results of a recent meta-analysis of 15,855 patients showing that both synthetic and PVS had similar objective cure rates that were superior to Burch colposuspension [4].…”
mentioning
confidence: 91%
“…More recently, the operation has been successfully used for primary SUI, as continence rates were better with greater patient satisfaction despite the higher incidence of postoperative voiding dysfunction compared with Burch colposuspension [3]. This finding is supported by results of a recent meta-analysis of 15,855 patients showing that both synthetic and PVS had similar objective cure rates that were superior to Burch colposuspension [4].…”
mentioning
confidence: 91%
“…Deval et al (23) and Ulmsten et al (18) reported subjective cure rates of 70% and 85% respectively in large studies on TVT for SUI , and cure rates of 74% have been reported on mid-urethral TVT for ISD (17). A recent systematic review of surgical treatments of SUI demonstrated similar cure rates in the MUS and RFS group and a trend towards a higher re-operation rate in the MUS group (24). Our subjective cure rate of 85% with bladder neck placement, after median 4 year follow up, compares favorably with the literature (Table 4).…”
Section: Cuaj -Original Researchmentioning
confidence: 95%
“…The authors have correctly cited the conclusion of the systematic review by Fusco et al [2], suggesting that, with regard to objective cure rates, synthetic slings might have been superior to Burch colposuspension. I would like to draw the authors' attention to a recent letter and reply [3] that questioned such a conclusion, particularly as the relevant Cochrane review [4] had concluded that there was no significant difference in the objective outcomes between synthetic slings and colposuspension.…”
Section: Dear Editormentioning
confidence: 97%
“…The cited systematic review [2] had included a trial of Blaparoscopic^colposuspension among the Bopenĝ roup and had applied meta-analysis to a secondary, rather than the primary, outcome of the Ward and Hilton study [5], the main RCT in the open group. Outcome switching could have been the reason behind a conclusion that is in variance with the Cochrane Review.…”
Section: Dear Editormentioning
confidence: 99%